Distinctive biochemistry profiles associated with hyperuricemia between Tibetans and Hans in China - Ren, Xue-Wen; Chen, Kang; Wu, Jue; Yang, Zhang-Lin; Ji, Tao; Zhang, Qing-Hong (Frontiers in Endocrinology, 2023)
We sought to identify distinct risk factors for hyperuricemia in native Tibetan and immigrant Han populations in Tibet, China.Methods: Three cohorts of male participants aged between 20 and 40 years were enrolled in this study. Biochemical parameters including serum uric acid (UA), fasting plasma glucose, insulin, lactate dehydrogenase (LDH), thyroxin, blood cell count, aminotransferase, and lipid profiles were analyzed. The association of risk factors with UA levels was evaluated using a multivariable line regression model. The effect of UA level on the biochemical parameters between the Hans and Tibetans was evaluated by two-way ANOVA.The prevalence of hyperuricemia (≥420 μmol/L) was 24.8 % (62/250) in the Hans, similar and 23.8% (29/136) in the Tibetans. In the regression analysis, the risk factors that were significantly associated with UA in Hans did not apply to Tibetans. Tibetans had higher fasting insulin (P<0.05) and LDH (P<0.01) levels, in contrast with lower levels of triglycerides (P<0.05), total cholesterol (P<0.01), and low-density lipoprotein-cholesterol (P<0.01) than Hans in normal UA populations. Biochemistry analysis revealed lower albumin levels (P<0.001) and higher levels of all aminotransaminase and especially alkaline phosphatase (P<0.01) in Tibetans than in Hans in both populations. Compared with Hans, Tibetans had lower serum levels of urea, creatinine, and electrolytes in the normal UA population, which were further exacerbated in the high UA population. Tibetans had comparable white blood cell counts as Hans in both normal and high UA populations. In contrast, the red blood cell count and hemoglobin concentration were much lower in Tibetans than in Hans under high UA conditions.The distinctive biochemistry between Tibetans and Hans may underlie the different etiologies of hyperuricemia in Tibet, China.